HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR SISWA DI MTS MARHALIM CAMPALAGIAN POLEWALI MANDAR - Naharuddin; Mustamin; Abdul Wahab; Ahmad; Muh Azhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the correlation between learning motivation and students' academic achievement in the subject of Akidah Akhlak at MTs Marhalim Campalagian, Polewali Mandar. The objectives of the study include: (1) describing the level of students' learning motivation; (2) describing students' academic achievement; and (3) analyzing the relationship between learning motivation and academic achievement. This quantitative study used a correlational design and involved the entire student population (N=51) because the number was less than 100 respondents. Data collection was carried out through documentation and questionnaire methods. Data analysis used the Pearson Product Moment correlation test. The results showed that the majority of students (70.59%) had learning motivation in the moderate category, with 36 students scoring between 92-110. Similarly, 70.59% of students showed academic achievement in the moderate category. The correlation analysis produced a significance value of 0.00 (p <0.05) and a correlation coefficient of 0.764. These findings indicate a strong positive correlation between learning motivation and students' academic achievement at MTs Marhalim Campalagian. Higher levels of motivation are positively correlated with better academic achievement. This finding underlines the important role of motivation as a determinant factor of students' learning success in the subject of Akidah Akhlak. Schools need to pay attention to and strive to improve students' learning motivation through various pedagogical strategies, such as creating a conducive learning environment, implementing innovative and engaging learning methods, and providing a fair and motivating reward system. Further research is recommended to identify other factors that influence students' academic achievement, as well as explore more effective intervention strategies to improve students' motivation and learning achievement, taking into account the local cultural context for the optimization of sustainable learning strategies.